The child in the middle: A roadmap for studying user experience for children - Alexandre, I.; Santana, P. (Children, Robots, and Virtual Agents: Present and Future Challenges Workshop in ACM Interaction Design and Children, 2021)
The goal of this paper is to identify the relevance and challenges that need to be addressed when developing research in user experience for children from 3 to 12 years old, while considering the involved ethical challenges. In particular, we identify a research roadmap for the development of a serious game whose purpose is to foster the exploration of the challenges regarding user experience for children. For such serious game, we suggest portraying a STEAM theme promoting specific sustainable development goals posed by the United Nations. In addition, we propose to follow a co-design and codevelopment approach, paying special care to prevent threats to the rights and privacy of the children, an interesting challenge itself. Additionally, we also identify the need for the devise of guidelines to be taken into consideration when it comes to improve child’s experience, to respect and identify related ethical issues, and to promote gender inclusion during the development of child-targeted serious games.